2012
DOI: 10.1017/s0016672312000341
|View full text |Cite
|
Sign up to set email alerts
|

Maximum likelihood estimation of individual inbreeding coefficients and null allele frequencies

Abstract: In this paper, we developed and compared several expectation-maximization (EM) algorithms to find maximum likelihood estimates of individual inbreeding coefficients using molecular marker information. The first method estimates the inbreeding coefficient for a single individual and assumes that allele frequencies are known without error. The second method jointly estimates inbreeding coefficients and allele frequencies for a set of individuals that have been genotyped at several loci. The third method generali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…In all scenarios examined, the new method presented here largely outperformed the original Hall et al (2012) method based on called genotypes, especially in cases of extremely low coverage, small sample sizes, and high error rates. Because the original method has been previously shown to outperform other methods based directly on genotypes (Hall et al 2012), the advantage of our method, in the presence of genotype uncertainty, should extend to these methods as well.…”
Section: (2012) Methods (Sfs) In Both Cases Two Priors Were Used: Ramentioning
confidence: 94%
See 3 more Smart Citations
“…In all scenarios examined, the new method presented here largely outperformed the original Hall et al (2012) method based on called genotypes, especially in cases of extremely low coverage, small sample sizes, and high error rates. Because the original method has been previously shown to outperform other methods based directly on genotypes (Hall et al 2012), the advantage of our method, in the presence of genotype uncertainty, should extend to these methods as well.…”
Section: (2012) Methods (Sfs) In Both Cases Two Priors Were Used: Ramentioning
confidence: 94%
“…Several methods have been published to infer per-individual inbreeding coefficients (Vogl et al 2002;Leutenegger et al 2003;Wang et al 2006;Moltke et al 2011), but all were designed for genotype (marker) data. Although all present slight improvements, Hall et al (2012) recently incorporated most features into a single EM algorithm and showed that it outperformed previous methods. Here, we have modified this algorithm to accommodate for NGS data, as well as an approximate EM algorithm that can help speed up convergence.…”
Section: (2012) Methods (Sfs) In Both Cases Two Priors Were Used: Ramentioning
confidence: 99%
See 2 more Smart Citations
“…These two effects can cause an over-or underestimation of the relatedness coefficient. Some methods can estimate the frequency of null alleles (e.g., Brookfield 1996; Vogl et al 2002;van Oosterhout et al 2004;Kalinowski et al 2006;Hall et al 2012;Dabrowski et al 2013). We thus model the probability that a genotype pair (Anderson and Weir 2007) or a genotype pattern or a genotype pair pattern is observed under the assumption that the true frequencies of alleles are already known.…”
Section: Theory and Modelingmentioning
confidence: 99%